Investigation of Manganese–Iron Oxide Materials based on Manganese Ores as Oxygen Carriers for Chemical Looping with Oxygen Uncoupling (CLOU). Issue 5 (29th April 2014) - Mohammad Pour, Nasim; Azimi, Golnar; Leion, Henrik; Rydén, Magnus; Mattisson, Tobias; Lyngfelt, Anders
Abstract: Oxygen carrier materials were synthesized using five different types of manganese ores with addition of iron oxide (Fe2 O3 ), and they were investigated for their reactivity and properties in chemical looping with oxygen uncoupling (CLOU). Two different Mn/Fe molar ratios (1:2 and 2:1) were examined. The samples were manufactured by using a lab‐scale extrusion method followed by sintering at 950 °C for 4 h. To measure their reactivity, the materials were exposed to gaseous CH4 and syngas (50:50 CO/H2 ) as well as solid fuel (petroleum coke), in a batch fluidized‐bed reactor. With CH4, the materials based on ores from Brazil and Gabon with a Mn/Fe molar ratio 2:1 showed the best reactivity. For reduction using syngas, samples based on Eastern European and South African ores provided higher amounts of oxygen equivalent, up to 3–5 % of their mass. To investigate the ability of the samples to release gas‐phase oxygen, solid fuel experiments using 0.1 g of petroleum coke in a bed of 10 g oxygen carrier were performed at 950 °C with Brazilian, Gabon, and Eastern European ores. In these solid fuel tests samples with a Mn/Fe molar ratio of 1:2 showed higher uncoupling rates. Based on X‐ray diffraction analysis, the primary phase detected in all fresh particles was the oxidized form of Mn y Fe1− y O x, that is, bixbyite [(Mn, Fe)2 O3 ]. All of the particles showed sufficiently high crushing strength (>2 N ) and a reasonable attrition resistance (attrition index <6 wt % h −1 ). This suggests that the materials could be suitable for practical applications. It is concluded that the oxygen carriers made by manganese ores have the potential to be used as oxygen carriers for chemical‐looping combustion and chemical looping with oxygen uncoupling. Abstract : Either ore: Oxygen carrier materials are synthesized using five different types of manganese ores with addition of Fe2 O3, and they are investigated for their reactivity and properties in chemical looping with oxygen uncoupling (CLOU). The results suggest that oxygen carriers made by manganese ores have the potential to be used as oxygen carriers for chemical‐looping combustion and CLOU with the main advantage of low cost and possibly also higher mechanical stability over the more pure materials.